Analysis of Harf Halq Intonation Patterns in Imperative Sentence Pronunciation Based on PRAAT Application-Based Frequency Values - Sri Yulia Yuliani,; Asep Sopian,; Hikmah Maulani, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to analyze intonation patterns in the pronunciation of imperative sentences in Arabic. Intonation is a pattern of pitch changes produced by the speaker when pronouncing a sentence or its parts, which greatly affects the meaning of the utterance. This research uses descriptive qualitative methods in the form of verbal data analysis. PRAAT application is used for spectral analysis and sound frequency measurement. The results showed that the common intonation patterns in Arabic imperative sentences are /2-3-1/ and /3-2-1/, in accordance with the theory proposed by Al-Aini. Of the six participants, four of them have intonation patterns that match the native speaker's speech patterns, while the other two participants show variations of intonation patterns that do not match. Factors such as mother tongue influence, inappropriate emphasis or nabr, and ignorance of intonation patterns contributed to the difference. The findings are expected to help in Arabic language teaching, particularly in the phonetic aspect of harf halq, as well as contributing to the fields of Arabic linguistics and Arabic language education.